Effect of Bio-Organic Fertilizer on Soil Organism in Experimental Oil Palm Plantation Cikabayan, Bogor, Indonesia - Widyastuti, Rahayu; Adiyaksa, Ivan Khofian; Wulandari, Dwi; Zuhud, Evrizal A M (Jurnal Ilmu Tanah dan Lingkungan, 2025)
The use of chemical-based fertilizer continuously without addition of organic matter may have hazardous effects on the environment. Numerous studies have shown that chemical-based fertilizers may disrupt the balance of soil properties, including physical, chemical, and biological properties. Bio-organic fertilizers have become one of the alternative answers to oil palm sustainability and a replacement for chemical-based fertilizers to promote and provide a better service to the soil and environment. This study aims to analyze the effect of application of biofertilizers combined with different dosages of organic matter (bio-organic fertilizers), i.e. 0 kg tree-1, 6 kg tree-1, and 12 kg tree-1, respectively. The study was conducted in Cikabayan Experimental Oil Palm Plantation, Bogor, West Java with 12 year-old-plant oil palm, from May to November 2023. The study showed an increase in the population density of the soil organisms after application of bio-organic fertilizers, especially with the dose of 6 kg tree-1. The change in the soil fauna community structure was also observed in this study, where Collembola dominated the ecosystem after fertilization. These findings offer practical strategies to mitigate the negative impacts of traditional fertilizers. Moreover, the study highlights the role of bio-organic fertilizers in enhancing soil biodiversity by increasing the populations of beneficial soil organisms.